Exhibition Reviews. Issue 1 (1st July 2021) - Hoffman, Sheila K.; Tanaka, Aya; Xue, Bai; Ng, Ni Na Camellia; Jiang, Mingyuan; McLarin, Ashleigh; Kearney, Sandra; Hotere-Barnes, Riria; Kim, Sumi
Abstract : Museum of Russian Icons, Clinton, Massachusetts by Sheila K. Hoffman Local Cultures Assisting Revitalization: 10 Years Since the Great East Japan Earthquake, National Museum of Ethology (Minpaku), Osaka by Aya Tanaka Tianjin Museum of Finance, Tianjin by Bai Xue Vegetation and Universe: The Collection of Flower and Bird Paintings, Zhejiang Provincial Museum, Hangzhou by Ni Na Camellia Ng Three Kingdoms: Unveiling the Story, Tokyo National Museum and Kyushu National Museum, Japan, and China Millennium Monument, Nanshan Museum, Wuzhong Museum, and Chengdu Wuhou Shrine, People's Republic of China by Mingyuan Jiang Tempest, Tasmanian Museum and Art Gallery, Hobart by Ashleigh McLarin Wonders from the South Australian Museum, South Australian Museum, Adelaide by Sandra Kearney Brett Graham, Tai Moana, Tai Tangata, Govett Brewster Art Gallery, New Plymouth by Riria Hotere-Barnes The "Inbetweenness" of the Korean Gallery at the Musée Guimet, Paris by Sumi Kim